Multiple Consecutive Cervicovaginal Cytology Specimens Confirm Persistent Colonization by Cokeromyces recurvatus: Case Report and Literature Review. (13th May 2022) - Lor, Keng; Hartley, Christopher P.; Pritt, Bobbi S.; Kemp, Anna M.; Swanson, Amy A.; Sturgis, Charles D.
Abstract : The published literature on cervicovaginal cytology includes fewer than ten reported cases of Cokeromyces recurvatus identified in Pap test samples. We report a unique case of an asymptomatic 27-year-old female with persistent gynecologic tract colonization by C. recurvatus in which distinctive fungal microorganisms were identified in three samples collected over three consecutive years.